2002
DOI: 10.1089/104454702753768052
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Acid Resistance of Enamel and Dentin by CO2Laser Irradiation with Sodium Fluoride Solution

Abstract: It can be concluded that CO2 laser irradiation with NaF solution has more caries-preventive effect than CO2 laser irradiation only at the enamel and dentin surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 21 publications
1
34
0
18
Order By: Relevance
“…While some studies reported a beneficial effect of a CO 2 12 or a Nd:YAG laser 26 on enamel erosion, dentin erosion could not be prevented by Nd:YAG laser irradiation. 27 In the present study, the output parameters for lasing enamel and dentin were chosen according to previous studies showing an increased acid resistance of enamel and dentin 10,13 or an increased enamel fluoride uptake 12,15 after CO 2 laser treatment. However, pulsed instead of continuous wave lasing was performed to confine possible modifications to a thin surface layer, without affecting the underlying hard tissue or pulp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some studies reported a beneficial effect of a CO 2 12 or a Nd:YAG laser 26 on enamel erosion, dentin erosion could not be prevented by Nd:YAG laser irradiation. 27 In the present study, the output parameters for lasing enamel and dentin were chosen according to previous studies showing an increased acid resistance of enamel and dentin 10,13 or an increased enamel fluoride uptake 12,15 after CO 2 laser treatment. However, pulsed instead of continuous wave lasing was performed to confine possible modifications to a thin surface layer, without affecting the underlying hard tissue or pulp.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Previous experiments showed that CO 2 laser irradiation induced a melting and recrystallinization process resulting in an increased acid resistance of dental hard tissues. [9][10][11] Moreover, laser irradiation might be also an approach to increase the efficacy of different fluoride solutions, such as amine 12 or sodium fluoride, 13,14 to reduce acid demineralisation. CO 2 laser irradiation increased the fluoride uptake in enamel 12,15 and facilitated the transformation from hydroxyapatite into fluorapatite.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In laser therapy, several factors related to exposure need to be considered: the wavelength and energy density of the laser, the irradiation time, the focal distance, and water cooling www.intechopen.com Morioka, et al, 1991;Fried, et al, 1996;Featherstone, et al, 1998;Hossain, et al, 2000;Young, et al, 2000;Hsu, et al, 2000;Tisai, et al, 2002;Kato, et al, 2003;Matson, et al, 2002;Apel, et al, 2002Apel, et al, , 2004Apel, et al, , 2005Rodrigues, et al, 2004;Westerman, et al, 2002;Nammour, et al, 2005Cecchini, et al, 2005Liu, et al, 2006;Fried, et al 2006;Castelan, et al, 2007). Furthermore, to achieve additional prevention, special attention has focused on laser irradiation, topical fluorides and remineralizing solution associations, showing very promising results (Hossain, et al, 2002;Delbem, et al, 2003;Chin-Ying, et al, 2004;Tepper et al, 2004;Rodrigues, et al, 2004;Kwon, et al, 2005;Ana, et al, 2006;Westerman, 2006;Tagliaferro et al, 2007).…”
Section: Laser and Caries Preventionmentioning
confidence: 99%